Doppelgänger dark energy: modified gravity with non-universal couplings after GW170817 - Amendola, Luca; Bettoni, Dario; Domènech Fuertes, Guillem; Gomes, Adalto R. (Journal of cosmology and astroparticle physics, 2018)
Gravitational Wave (GW) astronomy severely narrowed down the theoretical space for scalar-tensor theories. We propose a new class of attractor models for Horndeski action in which GWs propagate at the speed of light in the nearby universe but not in the past. To do so we derive new solutions to the interacting dark sector in which the ratio of dark energy and dark matter remains constant, which we refer to as doppelgänger dark energy (DDE). We then remove the interaction between dark matter and dark energy by a suitable change of variables. The accelerated expansion that (we) baryons observe is due to a conformal coupling to the dark energy scalar field. We show how in this context it is possible to find a non trivial subset of solutions in which GWs propagate at the speed of light only at low red-shifts. The model is an attractor, thus reaching the limit c T →1 relatively fast. However, the effect of baryons turns out to be non-negligible and severely constrains the form of the Lagrangian. In passing, we found that in the simplest DDE models the no-ghost conditions for perturbations require a non-universal coupling to gravity. In the end, we comment on possible ways to solve the lack of matter domination stage for DDE models.